Biofortification and phytoremediation - Zhao, F.J.; Mcgrath, S.P.
Producing nutritious and safe foods sufficiently and sustainably is the ultimate goal of modern agriculture. Past efforts have focused on increasing crop yields, but enhancing the concentrations of mineral micronutrients has become an urgent task because about half of the world population suffers from the malnutrition of iron, zinc, and selenium. Biofortification of these trace elements can be achieved through fertilization, crop breeding or biotechnology. On the other hand, soils contaminated with metals or metalloids may be cleaned up by phytoextraction that combines hyperaccumulation with high biomass production. Progress has been made in identifying inter-species and intra-species variation in trace element accumulation, and mechanistic understanding of some aspects of trace element transport and homeostasis in plants, but much remains to be elucidated.